Hydrogen embrittlement susceptibility of selective laser melted, and post-heat treated AISI 316 L and Inconel 718 steels - Mettinen, Mirka (My University, 2024)
Laser powder bed fusion is one of many additive manufacturing techniques where specimen is fabricated layer by layer via melting powder selectively with laser beam. Additive manufacturing provides benefits including reduced material needs and waste, closer localization of spare part production and suppressed warehouses. However, the microstructural features formed during the manufacturing process differs from a conventionally produced counterparts leading to modified mechanical properties and performance in various circumstances. Hydrogen embrittlement is a phenomenon that embrittles metals, where hydrogen absorbs into the lattice through high pressure gas environment or electrochemical reaction causing decrease in toughness. It is extensively studied phenomena in metal materials, but the mechanisms and factors enhancing brittleness are further uncertain. Thus, thorough research of hydrogen embrittlement behaviour in additively manufactured metals is necessary to prevent premature failures causing dreadful accidents. The aim of the thesis is to raise awareness of the current research findings promoting hydrogen embrittlement in selective laser melted AISI 316 L and Inconel 718 steels, involving microstructural features, fracture mechanisms and mechanical properties. Both steels manufactured by selective laser melting are subjected to several post-heat treatments and compared to each other and their conventionally produced counterparts, to discuss the most compatible post-processed steel for hydrogen environment. The selective laser melting reduces hydrogen embrittlement susceptibility in both materials which can be explained by the unique microstructure formed during the manufacturing process. Moreover, the properties and hydrogen embrittlement vulnerability were able to be altered with post-heat treatments. Hot isotopic pressing and heat treatment without polishing procedures of AISI 316 L exhibited the highest resistance with a minimal brittleness. For one’s part, homogenization plus one aging treatment showed the lowest hydrogen embrittlement behaviour in Inconel 718, yet it does not compare to AISI 316 L. The grain and cell boundaries acted as a hydrogen accumulation and diffusion paths in both steels, but the primary factors enhancing hydrogen embrittlement were separate. The focus in AISI 316 L was dislocation structure and density while the detrimental features of Inconel 718 were precipitants γ′, γ′′, δ and Laves phases. Based on the research results, AISI 316 L is more compatible steel for hydrogen environment, but the hot isotopic pressing treatment caused the lowest yield and tensile strengths, and the absence of surface polishing could be problematic in the place of use. Hydrogen embrittlement behavior of selective laser melted steels requires further studies to achieve thorough understanding of the phenomenon where the conclusions of the thesis provide potential investigation paths.

Materiaalia lisäävä valmistus on kasvava tulostustekniikka, jossa materiaalia lisätään kerros kerrokselta. Valmistustekniikalla on useita hyötyjä, kuten pienempi materiaali- ja varastotilojen tarve sekä tuotantojäte ja varaosatuotannon mahdollinen uudelleensijoitus lähemmäksi. Mikrorakenteelliset ominaisuudet kuitenkin eroavat tavanomaisella tavalla valmistetuista vastineista, mikä johtaa erilaisiin mekaanisiin ominaisuuksiin sekä suorituskykyyn vaihtelevissa olosuhteissa. Vetyhauraus on metalleja haurastuttava ilmiö, jossa vetyatomi absorboituu metallihilaan korkeapaineisessa vetykaasuympäristössä tai sähkökemiallisen reaktion myötä ja aiheuttaa sitkeyden heikkenemistä sekä hauraan murtumaan. Metallien vetyhaurastumista on laajalti tutkittu, mutta haurautta edistävät mekanismit ja tekijät ovat edelleen kiistanalaisia. Täten tulostustekniikalla valmistetun metallin perusteellinen vetyhaurauskäyttäytymisen tutkiminen on välttämätöntä ennenaikaisten murtumien estämiseksi. Opinnäytetyön tavoitteena on lisätä tietoisuutta ajankohtaisista tutkimustuloksista, jotka edistävät jauhepetisulatettujen AISI 316 L- ja Inconel 718 -terästen vetyhaurautta käyttämällä jauheen sulatustekniikkana kuitulaseria. Ilmiötä tutkitaan murtumismekanismien ja mikrorakenteellisten sekä mekaanisten ominaisuuksien näkökulmasta. Molemmille teräsmateriaaleille tehdään useita erilaisia jälkikäsittelyjä, joiden ominaisuuksia vertaillaan keskenään sekä tavanomaisella tavalla valmistettuihin vastineisiin. Tulosten perusteella pohditaan vety-ympäristöön yhteensopivampaa terästä ja lämpökäsittelytekniikkaa. Materiaalia lisäävä valmistus vähensi vetyhaurausherkkyyttä molemmissa materiaaleissa, mikä voidaan perustella jauhepetisulatuksen aikana muodostuneen ainutlaatuisen mikrorakenteen avulla. Lisäksi tutkittavien teräksien ominaisuuksia sekä vetyhaurausherkkyyttä oli mahdollista muokata lämpökäsittelyiden avulla. Suurin vetyhaurauden kestävyys havaittiin AISI 316 L teräksellä kuuman isostaattisen puristuskäsittelyn ja pintakäsittelemättömän lämpökäsittelyn jälkeen. Puolestaan Inconel 718:n yhden ikäännyttämisvaiheen sisältävä homogenisointikäsittely osoitti suurinta vetyhaurauskestävyyttä, mutta se ei kuitenkaan ole verrattavissa AISI 316 L teräkseen. Mikrorakenteen rae- ja solurajat toimivat vedyn kasaantumis- ja diffuusioasemina, mutta ensisijaiset vetyhaurautta edistävät tekijät erosivat tutkittavien teräksien välillä. Haitalliset ominaisuudet AISI 316 L teräksessä olivat dislokaatiorakenne sekä -tiheys ja Inconel 718: ssa γ′-, γ′′-, δ -saostumat ja Laves -faasit. Tulosten perusteella voidaan todeta, että AISI 316 L on ominaisuuksiltaan suotuisampi vaihtoehto, mutta kuuman isostaattisen puristuskäsitellyn teräksen myötö- ja vetolujuus olivat tutkimuksien heikoimpia sekä pintakäsittelemättömän teräksen pinnankarheus voi aiheuttaa ongelmia, jotka tulee ottaa huomioon käyttökohteen vaatimuksia ajatellen. Jauhepetisulatettujen metallien vetyhauras vaatii yhä syvempää tutkimusta ilmiön perusteellisen ymmärryksen saavuttamiseksi, mihin opinnäytetyö antaa potentiaalisia tutkimussuuntia.
Keywords: additive manufacturing, selective laser melting, hydrogen embrittlement, post-heat treatment, materiaalia lisäävä valmistus, materiaalin sulatus kuitulaserilla, vetyhauraus, lämpökäsittely